Effect of angle of incidence on roll damping derivatives of a delta wing - Crasta, Asha; Khan, Sher Afghan (RS Publication, 2014)
In the Present paper effect of angle of incidence on roll damping derivative of a delta wing with curved leading edges with attached shock case has been studied. A Strip theory is used in which strips at different span wise location are independent of each other. This combines with similitude to give a piston theory. The Present theory is valid only when the shock wave is attached with the leading edge of the wing. Effects of secondary wave reflection and viscosity have not been taken into account. Effect of leading edge bluntness also has been neglected. Results have been obtained for hypersonic flow of perfect gases over a wide range of angle of attack and Mach number.